Cold Rolling Deformation Characteristic of a Biomedical Beta Type Ti–25Nb–3Zr–2Sn–3Mo Alloy Plate and Its Influence on α Precipitated Phases and Room Temperature Mechanical Properties During Aging Treatment - Cheng, Jun; Li, Jinshan; Yu, Sen; Du, Zhaoxin; Zhang, Xiaoyong; Zhang, Wen; Gai, Jinyang; Wang, Hongchuan; Song, Hongjie; Yu, Zhentao (Frontiers in Bioengineering and Biotechnology, 2020)
The microstructure characteristics and texture evolution of a biomedical meta-stable beta Ti-25Nb-3Zr-2Sn-3Mo (TLM) (wt %) titanium alloy plate cold rolled at various reductions were studied in this article. <110> texture was easily formed in the TLM alloy plates and a large number of dislocation tangles were generated in the β matrix in the process of cold rolling deformation. The dislocation lines, dislocation cells, sub-grain boundaries and other crystal defects introduced during cold rolling had a great impact on the morphological characteristics and volume fraction of precipitated phases during aging. These typical crystal defects could be considered as the major triggers of the formation of second phases, and they could also shorten the time of β→α phase transformation. α precipitated phases with a size range of 150-500 nm were formed within the β matrix in the cold deformed 34 % in conjunction with aging specimen, resulted in the relatively high tensile strength of 931 MPa and the acceptable elongation of 6.9 %. When the TLM alloy plate was cold rolled at reduction of 60 % in conjunction with aging, the maximum value of ultimate strength (1005 MPa) was achieved, but the elongation value was relatively low owing to the formation of α precipitated phases with large size around the sub-grain boundaries. In this paper, the influence of crystal defects and sub-grain boundaries on the morphology characteristics and volume fraction of α precipitated phases and mechanical properties will be discussed in detail.